The Quality Learning of Extensive Reading with Synergetic Learning Approach - Fitriyana, Azizah; Hasanah, Mamluatul; Syuhadak (Institut Agama Islam Negeri Curup, 2025)
This research aims to measure the quality prediction of extensive reading learning with synergetic learning approach. This research begins with a phenomenon that reading skills in the PBA study program aim to achieve speaking skills, active students in making assignments and collecting them arranged in a disciplined and structured manner and the phenomenon of active learning in class, students exchange the results of their reading assignments and collaborate in presenting to their friends and Lecturer's experience in teaching extensive reading for more than 20 years. Departing from the curiosity of this phenomenon, the researcher will explore and analyze the factors that quality of learning extensive reading with synergetic learning approach. This research is a descriptive quantitative, data analysis using the Structural Equation Modeling Partial Least Square (SEM - PLS) method. The results showed that extensive reading complied with the Ministry of Education, Culture and Research's quality standards at 80%, a very good level, and had a positive impact on lecturer behavior, student behavior, the learning environment, educational materials, educational media, and the education system. Extensive reading meets the criteria of synergetic learning theory at 85%, which is a very good value. It has a positive impact on educational outcomes, including team building, shared goals, cooperative learning, problem solving, shared assessment, continuous learning, and feedback. The theoretical results of this research showed that the quality learning of the extensive reading with synergetic learning approach has a positive impact on input, process, output, and outcomes. These are important aspects that indicate Outcome-Based Education.